2018
DOI: 10.2147/cmar.s148677
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic potential of <em>APC </em>hypermethylation in esophageal cancer

Abstract: Background The hypermethylation of APC gene is observed in various cancers, including esophageal cancer (EC). However, the association between APC methylation and the initiation and progression of EC is poorly understood. Purpose and methods The current study systematically reviewed studies on abnormal methylation of APC in EC and quantitatively synthesized 18 studies by meta-analysis involving 1008 ECs, 570 Barrett’s esophagus (BE), and 782 controls. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“… 3 The prognosis of ESCC is poor, and patients have only 15%–25% of 5-year survival rates after diagnosis. 4 6 …”
Section: Introductionmentioning
confidence: 99%
“… 3 The prognosis of ESCC is poor, and patients have only 15%–25% of 5-year survival rates after diagnosis. 4 6 …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a significant increase in methylation was observed in correlation with tumor grade [ 20 ]. Similarly, in another study from 2018, a significant relationship was shown between esophageal cancer and APC promoter gene methylation [ 21 , 22 ]. In another meta-analysis of 2018, 2483 patients and 1218 controls from 31 studies were evaluated and the relationship between breast cancer and APC gene methylation was studied.…”
Section: Discussionmentioning
confidence: 84%
“…There was also a direct association between APC promoter hyper methylation and grade of tumor differentiation [ 57 ]. The Chinese esophageal cancer tumors had also higher rates of APC methylation compared with controls [ 171 ]. SFRP2 is one of the negative regulators of WNT signaling pathway.…”
Section: Signaling Pathwaysmentioning
confidence: 99%